Demographic and socioeconomic characterization of the Immediate Region of Teófilo Otoni, MG between 1991 and 2010 - Morais, Sérgio Lana; Lopes Júnior, Geraldo; Fernandes , Duval Magalhães (Revista Cerrados, 2023)
The Immediate Geographical Region of Teófilo Otoni (RGIm Teófilo Otoni) is composed of 27 municipalities and reveals itself in different demographic and infrastructural conditions from the other regions of the State of Minas Gerais, Brazil. In this sense, the objective of this article is to describe and evaluate the main demographic indicators for the municipalities that make up RGIm Teófilo Otoni between 1991 and 2010 for the purposes of general characterization based on this new spatial arrangement. The database used was obtained from repositories of planning and research institutions, such as the Brazilian Institute of Geography and Statistics (IBGE), Ministry of Health (DATASUS), and the João Pinheiro Foundation (FJP), and allowed the measurement of the following variables: total urban and rural population; distribution of the total population by age group according to sex; degree of urbanization; total fertility rate; annual geometric population growth rate; life expectancy at birth; mortality rate, and Municipal Human Development Index between the years 1991 and 2010, in addition to the migratory dynamics for the year 2010. The characterization allowed us to identify that, although there have been improvements in the demographic and socioeconomic conditions of this portion of the territory of Minas Gerais, the values found remained lagged in comparison to other regions of Minas Gerais. The perspective is that the data presented may help to understand some socio-spatial dynamics for a portion of the state that still lacks research and/or technical-scientific information.